Moral Reasoning at Work Rethinking Ethics in Organizations - Kvalnes, Øyvind (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
"I warmly recommend this book. It offers a fresh perspective on how to live with moral dilemmas in organizational life. Both practically-oriented and theoretically reasoned, this book is useful to teachers and students in academia, as well as employees in organizations." Anna-Maija Lämsä, Professor and Vice Dean, School of Business and Economics, University of Jyväskylä, Finland This book is open access under a CC-BY license. Moral dilemmas are a pervasive feature of working life. Moral Reasoning at Work offers a fresh perspective on how to live with them using ethics and moral psychology research. It argues that decision-makers must go beyond compliance and traditional approaches to ethics to prepare for moral dilemmas. The second edition has been updated with a range of examples from the author's more recent research, to reflect current issues affecting organizations in the digital age. With two new chapters on artificial intelligence and social media, this new edition provides an up-to-date overview of ethical challenges in organizations.